AB0979 MEVALONATE KINASE DEFICIENCY AT TREATMENT WITH CANAKINUMAB: RARE BELATED CUTANEOUS FEATURE. (13th June 2020) - Dos Santos Sobrín, R.; Lopez-Montesinos, B.; Martí Masanet, M.; Lacruz Pérez, L.; Calvo, I.
Abstract : Background: Mevalonate Kinase Deficiency (MKD) is an autosomal recessive autoinflammatory syndrome. Diagnostic criteria are based in clinical and genetic features (mutations in MVK gene) and its main treatment consists of blocking IL-1 1-5 . Objectives: To describe a case-series of a rare bleated cutaneous feature. Methods: From January 2004 to September 2019, all cases diagnosed of MKD have been reviewed. Results: 15 patients had MKD diagnosis (11 pathogenic mutations, homozygosis or double heterozygosis). Most common symptoms were oral and genital aphthous, abdominal pain, adenopathies and recurrent fever. Mean age of diagnosis was 10, 67 years old (8, 67 years later from the beginning of symptoms). Mean time of follow-up was 10 years. 3 patients developed this rare bleated cutaneous feature: suppurative hydrosadenitis. When the first injury appeared, all were at treatment with Canakinumab (mean time of treatment 4 years) and had 7, 67 years of MKD course. This comorbidity began as repeating abscesses in folds with apocrine glands and hair follicles (armpits, inguinal, anal and genital folds). 2 patients continued Canakinumab and 1 switched to Adalimumab because of severity of cutaneous involvement. Conclusion: This is the first case-series showing suppurative hydrosadenitis associated to MKD that has not been described in literature. Both theories have been found: as immune-mediated disease partnering this autoinflammatory syndrome (MKD) or as adverse event of treatment (anti-IL-1, less presumable). References: [1]Van der Meer JW, Simon A. The challenge of autoinflammatory síndromes: with an emphasis on hyper-IgD syndrome. Rheumatology 2016;55:23-29. [2]Arnal C, Modesto C. Sídnromes febriles periódicos hereditarios: nuevas perspectivas sobre su conocimiento clínico y genético. 2003;30(2):45-48. [3]Mulders-Manders C, Simon A. Hyper-IgD syndrome/mevalonate kinase deficiency: what is knew? Semin Immunopathol 2015;37:371-376. [4]Cush, J. Autoinflammatory Syndromes. Dermatol Clin 2013;31(3):471-480. [5]Moreira A, Torres B, Peruzzo J, et al. Skin symptoms as diagnostic clue for autoinflammatory diseases. An Bras Dermatol 2017;92(1):72-80. Disclosure of Interests: Raquel Dos Santos Sobrín: None declared, B Lopez-Montesinos: None declared, Miguel Martí Masanet: None declared, Lucía Lacruz Pérez: None declared, Inmaculada Calvo Grant/research support from: Bristol-Myers Squibb, Clementia, GlaxoSmithKline, Hoffman-La Roche, Merck Sharpe & Dohme, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, GlaxoSmithKline, Hoffman-La Roche, Novartis